The role of valorised plant proteins and phenolic compounds on the digestibility of foods: a short review of recent trends and future opportunities in addressing sustainability issues - Brennan, Charles Stephen (Frontiers in Food Science and Technology, 2024)
During the last 2–3 decades there has been increasing attention from academics, professionals and consumers about how phenolic compounds from plant based foods could enhance the nutritional quality of foods. This mini-review evaluates the focus given to the interactions phenolics have on the metabolic functions in foods and how these phenolic compounds can manipulate digestibility of both carbohydrates and proteins, and how this in turn can modulate metabolic disorders as well as microbiota. With an emphasis on research published in the last decade, the article also examines the potential of valorisation strategies to reutilise fractions which may have traditionally been lost in the food production operations. The reason for this focus is related to the pressing requirements of sustainability within the resource hungry food industry, and how we can create a culture of regenerative food innovation within the sectors.